Intertekstualitas Novel Jakarta Sebelum Pagi Karya Ziggy Zezsyazeoviennazabrizkie Dengan Karya Sastra Barat: Kajian Post-Strukturalis Julia Kristeva - Saputra, Aqmal Maulana; Firismanda, M.A Haris (Universitas Muhammadiyah Kotabumi, 2025)
Literary works never stand alone and are born from a situation of emptiness. However, literature is a connectedness of inter-discourse dialogue that lives in a cultural and socio-historical context. One work that is rich in such connectedness is the novel Jakarta Sebelum Pagi by Ziggy Zezsyazeoviennazabrizkie. Of course, Julia Kristeva's post-structuralist theory of intertextuality, which views text as part of a network of inter-discourses and permutations of other texts, is a relevant framework for analyzing this work. This research is important to see how contemporary Indonesian literature is connected both explicitly and implicitly with a wider network of texts, especially western literary works that can extensively describe how inter-textual dialogue is cross-cultural. This research uses a qualitative descriptive approach with content analysis techniques. The results of the analysis show that this novel builds dynamic intertextual relationships with various western literary works, especially through aspects of characterization, character development, representation of urban life, and social criticism. In general, this research shows that literature in forming narratives and meanings is always transformative, dynamic, and interactive across socio-historical and cultural boundaries.